Web Based Expert System in Area & Land Value Calculation and Faraid Distribution - Mohd Saad, Muhammad Solihin; Mohamad Rasli, Roznim (International Journal of Artificial Intelligence, 2022)
E-FaraidTanah is a web-based expert system that can help Muslims better understand Islamic Inheritance Law and calculates land distribution based on Faraid law. The main goal of this project is to develop the E-FaraidTanah prototype and to evaluate the user satisfaction. The methodology use throughout this project is an iterative and incremental model which offers the advantage of allowing the project improvement in a step-by-step basis. Hence, it is much easier to control risk and track errors at an early stage. E-FaraidTanah has been analyze based on usability testing through an online survey involving Muslim university students that measures percentages. Findings indicate that 82% of 30 respondents agreed that E-FaraidTanah performed well in terms of efficacy and efficiency. Thus, it is beneficial to assist society awareness on how Faraid property is divided and calculated.